(Invited) Finely Controlled Heterointerfaces between Ge(111) and Metallic Alloys or Insulators for Next Generation Ge-Based Devices. (18th August 2016) - Hamaya, Kohei; Yamada, Shinya; Kasahara, Kenji; Kanashima, Takeshi
Abstract : Heteroepitaxial growth of bcc metallic alloys or a high- k insulator on Ge(111) has been explored for next generation Ge-based devices. First, we introduce a finely controlled crystal growth technique of bcc-type ferromagnetic alloys on Ge(111). Next, we show that the Fermi level pinning is significantly suppressed at the high-quality bcc-alloys/Ge heterointerfaces. Using these kinds of structures, we can achieve spin injection and detection in n -Ge. Finally, we present a new approach to gate-stack structures for Ge-MOSFET. Even a crystalline high-k insulator can be grown epitaxially on Ge(111) and a high-quality heterointerface can be achieved. Also, reasonable electrical characteristics are obtained. These finely controlled heterointerfaces will open a way for developing new technologies in next generation Ge-based devices with low power consumption.